HUBUNGAN ANTARA INTENSITAS PEMERIKSAAN KEHAMILAN, FASILITAS PELAYANAN KESEHATAN, DAN KONSUMSI TABLET BESI DENGAN TINGKAT KELUHAN SELAMA KEHAMILAN - Marissa Indreswari; Hardinsyah Hardinsyah; M. Rizal Martua Damanik (Jurnal Gizi dan Pangan, 2008)
Pregnant mother is one of the group gristle nutrition. Pregnant mother need to do medical check during pregnancy to support quality of good health. Pregnancy inspection is suggested minimum four times during pregnancy. The aim of this study is to analyze correlation between intensity of pregnancy inspection, facility of health service and the iron tablet consumption with mount the sigh experienced during pregnancy.This study used thecross sectional study methodwith sample taking method by purposive in Kramat Jati Sub-district (East Jakarta) and Ragunan Sub-district (South Jakarta). Total sample taken for this study were 100 pregnant mothers(50 from each regional). Data obtained was processed by Microsoft Excel 2003 and analyzed by SPSS 13.0 for windows. Analyze data used Rank Correlation Spearman to know the correlation between variables.Results showed significant correlations betweeniron tablet consumption obedience with intensity of pregnancy inspection. Significant correlation was also shown by intensity of pregnancy inspection variable with facility of health service which got by pregnant mother during pregnancy inspection. This result study was strenghtened by previous study that showed intensity of pregnancy inspection to the health service had strong correlation with antenatal care which obtained by pregnant mother.